Cellular mechanisms underlying obesity-induced arterial stiffness - Aroor, Annayya R. (Am J Physiol Regul Integr Comp Physiol, 2018)
Obesity is an emerging pandemic driven by consumption of a diet rich in fat and highly refined carbohydrates (a Western diet) and a sedentary lifestyle in both children and adults. There is mounting evidence that arterial stiffness in obesity is an independent and strong predictor of cardiovascular disease (CVD), cognitive functional decline, and chronic kidney disease. Cardiovascular stiffness is a precursor to atherosclerosis, systolic hypertension, cardiac diastolic dysfunction, and impairment of coronary and cerebral flow. Moreover, premenopausal women lose the CVD protection normally afforded to them in the setting of obesity, insulin resistance, and diabetes, and this loss of CVD protection is inextricably linked to an increased propensity for arterial stiffness. Stiffness of endothelial and vascular smooth muscle cells, extracellular matrix remodeling, perivascular adipose tissue inflammation, and immune cell dysfunction contribute to the development of arterial stiffness in obesity. Enhanced endothelial cortical stiffness decreases endothelial generation of nitric oxide, and increased oxidative stress promotes destruction of nitric oxide. Our research over the past 5 years has underscored an important role of increased aldosterone and vascular mineralocorticoid receptor activation in driving development of cardiovascular stiffness, especially in females consuming a Western diet. In this review the cellular mechanisms of obesity-associated arterial stiffness are highlighted.